(untitled) (International Journal of Occupational Safety and Health, 2021)
The COVID-19 pandemic has wrecked havoc on the mankind and caused dramatic disruptions in personal and professional lives of the people. With economies at the verge of collapse, businesses pushed to a standstill, forced alterations in work environment, and uncertainty about the future, this global health crisis has severely impacted employees and organizations. The virus has not only impacted employees physically but also psychologically as they experienced plethora of intense emotional fluctuations. In this regard, the present study aims to synthesize and analyze the existing literature on the subject and present a conceptual framework to aid understanding of the emotional repercussions of pandemic for employees and organizations at large. The extensive review of literature suggests that the perilous crisis resulted in numerous negative emotional outcomes which majorly converge into three i.e. stress, burnout, and depression. This emotional turmoil gets further reflected in employees’ performance at work and thus a conceptual model is developed to holistically capture and present such varied impacts of pandemic on employees. The study also posits that the deleterious emotional impacts can have grave ramifications for the organizations and thus, seek immediate attention of the organizational leaders, managers, and policy makers. Against this backdrop, the practical implications of the study are mentioned and recommendations are made, that may help employees and organizations to survive and sustain any such future crisis situations.